2021
DOI: 10.1111/1756-185x.14121
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Japanese patients with systemic sclerosis complicated with calcinosis

Abstract: Aim Calcinosis is often observed in systemic sclerosis (SSc), but its pathogenesis remains unclear. The aim of the present study was to explore the association of clinical features with calcinosis in patients with SSc. Methods A retrospective cohort study was performed analyzing 416 SSc patients from our SSc database. We examined the clinical features with relation to calcinosis and SSc. Results Calcinosis was observed in 24.0% of patients with SSc. The group with calcinosis comprised more female patients (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Many studies have established that calcinosis in SSc is associated with features of vascular dysfunction including loss of digital pulp, acro-osteolysis and presence of digital pitting scars [2,6,8,21,23,26 ▪▪ ,27–30]. A Japanese cross-sectional study showed that calcinosis in the facial region is commonly associated with multiple external root resorption which is akin to loss of digital pulp in the hands [19].…”
Section: Associated Disease Characterstics and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have established that calcinosis in SSc is associated with features of vascular dysfunction including loss of digital pulp, acro-osteolysis and presence of digital pitting scars [2,6,8,21,23,26 ▪▪ ,27–30]. A Japanese cross-sectional study showed that calcinosis in the facial region is commonly associated with multiple external root resorption which is akin to loss of digital pulp in the hands [19].…”
Section: Associated Disease Characterstics and Pathogenesismentioning
confidence: 99%
“…Based on physical examination or clinically indicated x-rays, it is more common in Caucasians (up to 38%) compared to Asian ethnicity (9%) [2,3]. It has a prevalence of 10% in North Africa [4], 29% in the Middle East, [5] and 24% in Japan [6]. However, subclinical calcinosis detected on imaging studies was found to be present in up to 50% of patients within 4 years of disease onset in Japan [7 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have established that calcinosis in SSc is associated with features of vascular dysfunction including loss of digital pulp, acro-osteolysis and presence of digital pitting scars [2,6,8,20,22,25 ▪▪ ,26–29]. A Japanese cross-sectional study showed that calcinosis in the facial region is commonly associated with multiple external root resorption, which is akin to the loss of digital pulp in the hands [30].…”
Section: Associated Disease Characterstics and Pathogenesismentioning
confidence: 99%
“…On the basis of physical examination or clinically indicated x-rays, it is more common in whites (up to 38%) compared with Asian ethnicity (9%) [2,3]. It has a prevalence of 10% in North Africa [4], 29% in the Middle East [5] and 24% in Japan [6]. However, subclinical calcinosis detected on imaging studies was found to be present in up to 50% of patients within 4 years of disease onset in Japan [7 ▪ ].…”
Section: Introductionmentioning
confidence: 99%